Investigation on gaseous and electrochemical hydrogen storage performances of as-cast and milled Ti1.1Fe0.9Ni0.1 and Ti1.09Mg0.01Fe0.9Ni0.1 alloys. (18th January 2018) - Shang, Hongwei; Zhang, Yanghuan; Li, Yaqin; Qi, Yan; Guo, Shihai; Zhao, Dongliang
Abstract: The AB-type Ti1.1 Fe0.9 Ni0.1 (Mg0 for short) and Ti1.09 Mg0.01 Fe0.9 Ni0.1 (Mg0.01 for short) alloys were fabricated by vacuum induction melting and mechanical milling. The effects of partly substituting Ti with Mg and/or mechanical milling on the structure, morphology, gaseous thermodynamics and kinetics, and electrochemical performances were studied. The results reveal that the as-cast Mg0 alloy contains the main phase TiFe and a small number of TiNi3 and Ti2 Ni phases. Substituting Ti with Mg and/or mechanical milling results in the disappearance of the secondary phases. The discharge capacities of the as-cast Mg0 and Mg0.01 alloys are 12.6 and 8.8 mAh g −1, which increase to 52.6 and 80.4 mAh g −1 after 5 h of mechanical milling. By milling the as-cast alloy powders with carbonyl nickel powders, they are greatly enhanced to 191.6 mAh g −1 for the Mg0 +7.5 wt% Ni alloy and 205.9 mAh g −1 for the Mg0.01 +5 wt% Ni alloy at the current density of 60 mA g −1, respectively. The values of dehydrogenation enthalpy (Δ H des ) and dehydrogenation activation energy ( E des (a) ) are very small, meaning that the thermal stability and the desorption kinetics of the hydrides are not the key influence factors for the discharge capacity. The reduction of the particle size and the generation of the new surfaces without oxide layers have slight improvements on the discharge capacity, while the enhancement of the charge transfer ability of the surfaces of the alloy particles can significantly promote the electrochemical reaction of the alloy electrodes. Highlights: TiFe-based electrode alloys with high capacity are prepared. Ti and Fe in the alloy are partly substituted by Mg and Ni respectively. Effects of elements substitution and/or mechanical milling on the structure and properties are investigated. Thermodynamics, kinetics and electrochemical properties of the alloys are tested. Controlling factors of electrochemical hydrogen storage of the alloys are investigated.